Laryngeal cancer incidence trends in the United States over 2000-2020: a population-based analysis - Seyed Ehsan Mousavi; Mehran Ilaghi; Armin Aslani; Morvarid Najafi; Zahra Yekta; Seyed Aria Nejadghaderi (BMC, 2024)
Abstract Introduction Laryngeal cancers account for one-third of all head and neck cancers. We aimed to report the incidence trends of laryngeal cancer over 2000-2020 in the United States (US), by age, sex, race/ethnicity, and histological subtypes. Methods Data from the Surveillance, Epidemiology, and End Results 22 database were used to identify patients with laryngeal cancer based on the International Classification of Diseases for Oncology, version 3. Age-standardized incidence rates (ASIRs) for laryngeal cancer, adjusted for reporting delays, were calculated. The Joinpoint Regression Program was then utilized to determine annual percent changes (APCs) and average annual percent changes (AAPCs) in the trends. The analysis excluded data from 2020 to prevent potential bias related to the COVID-19 pandemic. Results A total of 104,991 cases of laryngeal cancer were identified in the US from 2000 to 2019. Squamous cell carcinoma was the predominant subtype, accounting for 94.53% of cases. Above 73.20% occurred among non-Hispanic whites, with the highest incidence observed among individuals aged 55-69 years (46.71%). The ASIRs were 5.98 and 1.25 per 100,000 population for men and women, respectively. Over 2000-2019, there was a significant reduction in ASIRs for laryngeal cancer in both sexes. Non-Hispanic black men exhibited the highest ASIR (9.13 per 100,000) and the largest decline in the ASIRs over 2000-2019 (AAPC: -3.26%). Conclusions Laryngeal cancer incidence rates showed a decline from 2000 to 2019, in addition to 2020, during the COVID-19 pandemic. Additional research is required to investigate risk factors and their influence on incidence rates of laryngeal cancer.